Subjetivação e poder disciplinar na proposta de reintegração social na EJA no Sistema Prisional em Bragança/Pa - ALVES, Fabricio Gama (2021)
The relevance of providing education for juveniles and adults deprived of their liberty in penal houses is advocated as a guarantee of law in international, national, state and local laws, in order to provide opportunities for the reintegration of these invisible subjects in society. In this sense, the present study aims to analyze the modes of subjectivation of the person deprived of liberty and the technologies of disciplinary power in the proposal of social reintegration in Youth and Adult Education (EJA) in the Prison System in Bragança/PA. Thus, we seek to reflect on penalties in the historical perspective of prison and penal system between the seventeenth to the twentieth century; understand the meanings of prison education in the context of educational policy at national, state and municipal levels; to analyze the proposal of social reintegration in EJA in the prison system of Bragança/PA and to perceive the modes of subjectivation and the technologies of disciplinary power exercised in the prison system. The research is a qualitative approach, conducted at the Regional Recovery Center of Bragança / PA (CRRB) with those responsible for implementing the project of EJA in the unit. Data collection in the empirical field occurred through participant observation, documentary analysis and structured interviews conducted with the direction of the prison unit, the social reintegration coordination, the pedagogical coordination and the teachers of the 1st and 2nd stages of the EJA. fundamental. The results of this research show that the educational actions in the recovery center boil down to the lack of an adequate physical structure for the classes of the EJA, lack of specific continuing training by the competent bodies, such as the Pará State Department of Education (SEDUC), Of Bragança/PA (SEMED) and the Superintendence of the Pará State Penitentiary System (SUSIPE), to the servants who deal directly and indirectly with the formal education in the prison unit, planning not consistent with the reality of the prison public and its adversities. , and methodological strategies that do not favor the teaching-learning of the deprived of freedom as their emancipation as a citizen. It is concluded that in the field of educational public policies for those deprived of their liberty in penal establishments, the speeches and governmental actions are based on the strategies, maneuvers, tactics of exercising the technologies of disciplinary power through control, deprivation of these subjects. However, it appears that the discourses disseminated in the legal documents end up being fallacious, demobilized by interests that permeate governmental groups in a power relationship, weakening the implementation of these rights policies in prisons.